2022: Indonesia's Economic Recovery - Arismaya, Anisa Dewi (Jibaku: Jurnal Ilmiah Bisnis, Manajemen dan Akuntansi, 2023)
The world's economic condition was made into a crisis due to the effects of the Covid-19 pandemic, including in Indonesia. Indonesia is one of the countries that has experienced the impact of a decline and economic slowdown from 2019 to 2021. The Covid-19 pandemic has not only had an economic impact but also has an impact on health, social and education due to the government Lockdown which requires all people to be active. inside the house. Policies continue to be carried out to improve the economy Back to normal, one of which is the National Economic Recovery (PEN) policy by the Indonesian government. Through PEN, all aspects are assisted by the disbursement of funds from the State Budget to assist various aspects ranging from education, social to economic so that all economic activities continue to run. The government divided the PEN program into three parts, namely Stimulus 1, Stimulus 2, and Stimulus 3 and succeeded in helping Indonesia's economic recovery until 2022. Abstrak Kondisi ekonomi dunia dibuat krisis akibat dampak pandemi Covid19, termasuk di Indonesia. Indonesia merupakan salah satu negara yang mengalami dampak penurunan dan perlambatan ekonomi dari tahun 2019 ke tahun 2021. Pandemi Covid-19 tidak hanya berdampak pada ekonomi tetapi juga berdampak pada kesehatan, sosial dan pendidikan akibat Lockdown pemerintah yang menuntut semua orang untuk aktif. di dalam rumah. Kebijakan terus dilakukan untuk meningkatkan perekonomian Kembali normal, salah satunya adalah kebijakan Pemulihan Ekonomi Nasional (PEN) oleh pemerintah Indonesia. Melalui PEN, semua aspek dibantu kucuran dana dari APBN untuk membantu berbagai aspek mulai dari pendidikan, sosial hingga ekonomi agar semua kegiatan ekonomi tetap berjalan. Pemerintah membagi program PEN menjadi tiga bagian yaitu Stimulus 1, Stimulus 2, dan Stimulus 3 dan berhasil membantu pemulihan ekonomi Indonesia hingga tahun 2022.